2006
DOI: 10.1097/01.dad.0000183701.67366.c7
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Distinction Between Merkel Cell Carcinoma and Small Cell Carcinoma of the Lung

Abstract: We assessed the usefulness of several immunohistochemical stains in distinguishing these two neoplasms, including cytokeratin 7, cytokeratin 20 (CK20), neuron-specific enolase, chromogranin, synaptophysin, neurofilaments (NF), thyroid-transcription factor-1 (TTF-1), CD56 antigen, S-100 protein, vimentin, c-erbB-2 oncoprotein, and CD117 antigen. All 13 cases of Merkel cell carcinoma evaluated were positive for CK20, and negative for TTF-1. Twelve of 13 Merkel cell carcinoma cases were positive for NF. Eleven of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
155
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(168 citation statements)
references
References 54 publications
6
155
0
7
Order By: Relevance
“…This is a smaller number of positive cases than that reported previously, as the older literature cites that 75-90% of cases are usually positive. [16][17][18][19] However, this finding is similar to that reported by Bobos et al, 32 who found that only 15% of cases of Merkel cell carcinoma expressed KIT. The staining we observed was primarily diffuse and weak (Figure 1c) compared to the staining for CD117 observed in GISTs (our positive external control).…”
Section: Discussionsupporting
confidence: 90%
“…This is a smaller number of positive cases than that reported previously, as the older literature cites that 75-90% of cases are usually positive. [16][17][18][19] However, this finding is similar to that reported by Bobos et al, 32 who found that only 15% of cases of Merkel cell carcinoma expressed KIT. The staining we observed was primarily diffuse and weak (Figure 1c) compared to the staining for CD117 observed in GISTs (our positive external control).…”
Section: Discussionsupporting
confidence: 90%
“…Eventually 763 cases of cutaneous Merkel cell carcinoma were retrieved from the English literature and included in our review. 15,[18][19][20][21][22][23][24][25][26][27][28][29] …”
Section: Case Selectionmentioning
confidence: 99%
“…14 Because neuroendocrine carcinoma subtyping for site of origin is critical for clinical management, research has been dedicated to finding site and subtype-specific diagnostic markers. [15][16][17][18] Several biomarkers have been utilized to determine tumor subtype. eg, calcitonin is expressed by a majority of medullary thyroid carcinomas, and CK20 is characteristically expressed in Merkel cell carcinoma.…”
mentioning
confidence: 99%
“…eg, calcitonin is expressed by a majority of medullary thyroid carcinomas, and CK20 is characteristically expressed in Merkel cell carcinoma. 15,16 Some authors have proposed a panel of immunohistochemical stains (CDX-2, PDX-1, NESP-55, TTF-1, PAX8) to distinguish between differentiated gastrointestinal, pancreatic, and pulmonary neuroendocrine carcinoma with some success in tumor specificity; 17,18 however, this approach has seen limited utility in clinical practice due to relatively low sensitivities. Functional neuroendocrine carcinoma may have characteristic serology results and clinical presentation (eg, gastrinoma, insulinoma, etc.).…”
mentioning
confidence: 99%